Perceptions Des Nuisances Environnementales Liées Aux Déchets Solides Ménagers Dans Les Centres Urbains Du Nord-Bénin : Cas Des Villes De Parakou, Djougou, Kandi Et Malanville - Babio Sanni; Baloubi Makodjami David; Houssou Sègbè Christophe (European Scientific Journal, ESJ, 2016)
The cities of Parakou, Djougou, Kandi and Malanville in the north of Benin have difficulty in eliminating dispose of waste produced by households in ecological way. This research was initiated to analyze the attitudes and understanding of environmental problems related to poor management of DSM by people of north Benin. To achieve this objective, a survey was conducted on the perception of environmental damage related to waste with 585 heads of households from August 2014 to March 2015. The city of residence, gender, age, marital status, level education, income, socio professional category are characteristics that were selected for the statistical analysis Khi2. Results showed 100% a significant statistical link between environmental pollution and city of residence (χ2 = 153.135; DF = 12; Pvalue = 0.000 <0.05). No statistically significant association was found between perceived environmental nuisances and sex (χ2 = 2.035; DF = 4; PValue = 0.729> 0.05) ; age (χ2 = 19.189, DF = 16; P-Value = 0.259> 0.05) ; marital status (χ2 = 20.809, DF = 12; P-Value = 0.053> 0.05 and income of respondents (χ2 = 32.273, DF = 32; P-Value = 0.453> 0.05). However in Djougou, a highly significant associative link was observed between respondents with incomes ranging from 100,001 to 150,000 and the air pollution (χ2 = 11.96, DF = 32; P-value = 0.000 <0.05). It is the same for the pollution of rivers in this income bracket in Parakou (χ2 = 5.85; DF = 24; Pvalue = 0.004 <0.05) and Kandi (χ2 = 6 04; DF = 10; P-value = 0.000 <. 0.05). Moreover, the level of education (χ2 = 14.728, DF = 12; P-Value = 0.257> 0.05) and occupation of the individuals interviewed (χ2 = 59.060, DF = 40; P-Value = 0.026 <0.05) determine their perceptions of environmental damage related to DSM. In total, city of residence, education level and occupation of individuals are the most, significant determiners in the perception of environmental damage related to the solid household waste.